Pharmacokinetics and Pharmacodynamics of Meloxicam in East Asian Populations: The Role of Ethnicity on Drug Response. (23rd November 2017) - Aoyama, Takahiko; Ishida, Yoshimasa; Kaneko, Masato; Miyamoto, Aoi; Saito, Yoshiro; Tohkin, Masahiro; Kawai, Shinichi; Matsumoto, Yoshiaki
Abstract : We aimed to reanalyze the differences in the pharmacokinetics (PKs) of meloxicam in East Asian populations based on a population approach using previously published data and to investigate the factors found in population PK analysis that affect the pharmacodynamics (PDs) of meloxicam. Population PK analysis was performed in 119 healthy male subjects (30 Japanese, 30 Chinese, 29 Korean, and 30 white) under strictly controlled trial conditions with regulated meals and a single lot of the drug. We found that CYP2C9 genotype and lean body mass were statistically significant predictors of clearance and volume of distribution, respectively. A statistical significant difference in the PK parameters between ethnic groups could not be identified. Simulations using PK/PD models showed that CYP2C9 genotype is the factor that affects the PDs of meloxicam. The genetic polymorphisms highlighted in this study would be beneficial for conducting clinical trials in East Asians with similar genetic backgrounds.